Pojavljanje medicinskih sester v javnih medijih - Karoli, Barbara (Obzornik zdravstvene nege, 2007)
The activities of nurses are related to illness and health and the activities of journalists are related to the filed of information. Mostly, nurses are of female sex and their role also reflects the role of women in society. Mass media are conveying their version of realty to the public, and they also show how much the nurses are really valued and what their public image is like. Thesource of the data was newspaper Delo, year 2003. Data were analysed with quantitative method. The appearance of words nurse and nursing was the criterion. One of the results shows the highest frequency of their use in January, April and November.
Keywords: communication medium; Časopisi; Health Education; medicinske sestre; mediji; Newspapers; Nursing Care; Zdravstvena nega; Zdravstvena vzgoja